FLOW INJECTION SPECTROPHOTOMETRIC DETERMINATION OF NARINGENIN IN SUPPLEMENTS USING SOLID-PHASE REACTOR CONTAINING IMMOBILIZED MANGANESE DIOXIDE - Mashhadani, Israa M Jawad Al; Abed, Sadeem Subhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Naringenin (NAR) is a part of the human daily diet, and it plays an important role in human health for its biological functions. This study describes a new, sensitive, simple, and accurate method for determining NAR in supplements. Methods: The method is based on oxidative coupling reaction between NAR and N, N-dimethyl-p-phenylenediamine in an alkaline medium using manganese dioxide immobilized in cellulose acetate as online oxidant agent to form a colored product which can be monitored at λ max598 nm. Results: Several operating parameters such as reactor column length, particles size, chemicals, and physicals reaction conditions were studied. The proposed method was sensitive and good repeatable, the linear range of NAR concentration was from 1 to 70 μg/ml with a limit of detection of 0.292 μg/ml, and recovery range of analysis was 99.55–100.48%. Conclusion: The proposed method was successfully applied for determining NAR in supplements.